2020
DOI: 10.1038/s41598-020-69243-0
|View full text |Cite
|
Sign up to set email alerts
|

Tinnitus and risk of Alzheimer’s and Parkinson’s disease: a retrospective nationwide population-based cohort study

Abstract: Previous studies have shown that central auditory dysfunction without severe peripheral hearing loss was associated with higher incidences of cognitive decline and Alzheimer's dementia 11,12. Both hearing loss and central auditory dysfunction are associated with higher risk of developing dementia 5-10 years later 13. Uhlmann et al. 14 demonstrated an association of hearing impairment and Alzheimer's dementia. There may be a pathophysiological interplay of hearing impairment and neurodegeneration. Although the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Tinnitus distress seems to negatively affect general or crystallized intelligence and executive functions while not influencing processing speed. This finding is novel given the nature of applied methodologies and the withingroup analysis in contrast to between-group findings of lower intelligence 27,35,37 , various impaired cognitive www.nature.com/scientificreports/ abilities except long-term memory 54 , increased risk of Alzheimer's and Parkinson's disease 55 , and lower TMT performance 27,[34][35][36] in tinnitus patients. In some studies these behavioral findings were further corroborated by neurophysiology, mostly in the form of longer latencies of standard event-related EEG components in auditory oddball tasks 54,56 .…”
Section: Discussionmentioning
confidence: 99%
“…Tinnitus distress seems to negatively affect general or crystallized intelligence and executive functions while not influencing processing speed. This finding is novel given the nature of applied methodologies and the withingroup analysis in contrast to between-group findings of lower intelligence 27,35,37 , various impaired cognitive www.nature.com/scientificreports/ abilities except long-term memory 54 , increased risk of Alzheimer's and Parkinson's disease 55 , and lower TMT performance 27,[34][35][36] in tinnitus patients. In some studies these behavioral findings were further corroborated by neurophysiology, mostly in the form of longer latencies of standard event-related EEG components in auditory oddball tasks 54,56 .…”
Section: Discussionmentioning
confidence: 99%
“…Because of this high comorbidity, tinnitus has been often assumed to impair cognition (Hallam et al, 2004;Savastano, 2008;Tegg-Quinn et al, 2016;Chu et al, 2020;Lee, 2020). For example, Tegg-Quinn et al (2016) reviewed 18 relevant studies to show an association between tinnitus and some aspects of cognitive function, such as executive control of attention.…”
Section: Introductionmentioning
confidence: 99%
“…In a meta-analysis study involving 38 records from 1,863 participants, Clarke et al (2020) found that tinnitus is additionally associated with lower processing speed and poorer short-term memory. Based on a national population retrospective study, Chu et al (2020) showed that tinnitus is an independent risk factor for subsequent Alzheimer's and Parkinson's disease, suggesting a role of tinnitus in age-related cognitive decline.…”
Section: Introductionmentioning
confidence: 99%
“…The similar results obtained in the OCT measurements suggested that there could be an underlying neurodegenerative condition and tinnitus could be the first finding of this neurodegeneration. In a recent population-based cohort study on this subject, it was reported that there could be a correlation between the presence of tinnitus and the future development of neurodegenerative diseases such as PD and AD [Chu et al, 2020]. In that study of 12,657 patients with tinnitus and 25,314 healthy individuals without tinnitus, the study participants were evaluated in respect of the development of neurodegenerative disease after a mean follow-up period of 7.42 years (range, 6.09-8.71 years).…”
Section: Discussionmentioning
confidence: 94%